Dietary patterns are associated with adolescent growth in China: a latent class analysis - Jin, Bingxin; An, Danyan (Frontiers in Nutrition, 2026)
BackgroundAdolescents’ growth and development are closely related to dietary patterns, yet evidence on the relationship between overall dietary patterns and adolescent growth in contemporary China is limited. This study aimed to identify major dietary patterns among Chinese adolescents and examine their associations with height and height-for-age z-scores (HAZ).MethodsIn this cross-sectional analysis of 2,466 adolescents (age 10–15) from the China Family Panel Studies (2012), dietary patterns derived by latent class analysis were examined in relation to parent-reported height. Dietary assessment used eight binary food-group indicators for past-week consumption; height was reported by a parent or guardian. Associations were estimated using multivariable linear regression and reported as adjusted HAZ differences (and corresponding absolute height differences in centimeters).ResultsThree distinct dietary patterns were identified: Pattern 1 (Meat-Egg Traditional), Pattern 2 (Diverse Protein-Rich), and Pattern 3 (Comprehensive Nutrient-Balanced). In the fully adjusted models, adolescents in Pattern 3 were on average 3.31 cm taller than those in Pattern 1 (p < 0.001). Pattern 2 also showed a moderate positive association, with participants being approximately 2.00 cm taller than those in Pattern 1 (p = 0.003). Findings for HAZ were consistent with those for absolute height.ConclusionThese findings suggest that a comprehensive, nutrient-balanced dietary pattern is positively associated with adolescent growth. Promoting nutrient-rich, diversified diets during adolescence could help maximize growth potential and improve developmental outcomes in youth.